(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
The short-term and long-term impacts of government spending and taxes, which are examples of fiscal policy, are the main focus of this study. The findings suggest that fiscal incentives and higher government spending are examples of expansionary fiscal policies that effectively increase aggregate demand, leading to economic growth and lower unemployment. Using a qualitative research methodology, this study aims to analyze the impact of fiscal policy on aggregate demand in Indonesia in 2024. Information is collected from various sources, including scientific articles and official documents, including the State Budget (APBN), tax laws, and economic data from relevant institutions in Indonesia. To keep prices stable and the national budget deficit under control, fiscal policy must be balanced. Overcoming local and global economic headwinds in 2024 requires a thorough understanding of the dynamics of fiscal policy and its impact on aggregate demand, which this study provides.